Protection of electricity distribution networks - Gers, Juan M.; Holmes, E. J. 1928- (The Institution of Engineering and Technology, 2011)
High quality electrical service is everyday more stringent in utilities and industrial facilities around the world. One of the main players to achieve this is the protection system, which has to be reliable, fast and with a good cost/benefit ratio. This book refers to most aspects of electrical protections, with emphasis on Distribution Systems. Protection of generation and transmission systems are also treated in the text. References to modern topics such as the Distributed Generation, Smart Grid and Standard IEC 61850 have been introduced. Written by two well experienced engineers who combine a comprehensive theoretical background with examples and exercises, this book will allow the reader to easily follow the ideas explored. The book will be valuable to pre and postgraduate students, design, maintenance and consulting engineers as well as instructors looking for proper references.